2013
DOI: 10.1634/theoncologist.2013-0015
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Body Mass Index on Survival in Veterans With Multiple Myeloma

Abstract: Learning Objectives Describe the association between baseline BMI, weight loss, and survival in MM. Explain the importance of BMI and baseline weight loss as part of the standard history obtained in patients with MM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 33 publications
1
34
1
Order By: Relevance
“…Mean BMI was calculated based upon height and weight measurements before MGUS diagnosis. 26 BMI was categorized as underweight (<18·5 kg/m 2 ), normal-weight (18·5–24·9 kg/m 2 ), overweight (25–29·9 kg/m 2 ), or obese (≥30 kg/m 2 ). Race was categorized as white, black, or other.…”
Section: Methodsmentioning
confidence: 99%
“…Mean BMI was calculated based upon height and weight measurements before MGUS diagnosis. 26 BMI was categorized as underweight (<18·5 kg/m 2 ), normal-weight (18·5–24·9 kg/m 2 ), overweight (25–29·9 kg/m 2 ), or obese (≥30 kg/m 2 ). Race was categorized as white, black, or other.…”
Section: Methodsmentioning
confidence: 99%
“…However, the data are inconsistent for breast cancer (11) and pancreatic cancer (12, 13), and no associations have been observed in ovarian cancer (14), colorectal cancer (15), lymphoma (14), pancreatic cancer, or esophageal cancer (16). In contrast, higher BMI at diagnosis has been associated with better prognosis in acute myeloid leukemia (17), multiple myeloma (18), head and neck cancers (19), and among women with non-Hodgkins lymphoma (9). There are scant data on the effects of BMI at diagnosis among other populations of cancer patients, and few analyses have made comparisons across multiple cancer types or across different stages of cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…It is becoming clear, however, that obesity and diabetes can accelerate cancer progression, tumor growth or drug resistance in the marrow. Specifically for multiple myeloma (MM), although individual studies have disagreed [1], the most recent pooled analysis of 20 prospective studies found clear associations between increased risk of death from MM in patients with a higher body mass index (BMI) during early adulthood, as well as higher BMI and higher waist circumferences at study entry [2]. In addition, Bredella et al found that patients who were recently diagnosed with MM had higher abdominal fat cross-sectional areas and higher fat metabolic activity compared to patients with Monoclonal Gammopathy of Undetermined Significance (MGUS) [3].…”
Section: Obesity Adipose Tissue and Cancermentioning
confidence: 99%